[11C]Cyanation of arylboronic acids in aqueous solutions. Issue 49 (5th June 2017) - Ma, Longle; Placzek, Michael S.; Hooker, Jacob M.; Vasdev, Neil; Liang, Steven H.
Abstract : A copper-mediated 11 C-cyanation method employing arylboronic acids and [ 11 C]HCN in aqueous solutions has been developed to provide a wide range of aromatic 11 C-nitriles. Abstract : A copper-mediated 11 C-cyanation method employing arylboronic acids and [ 11 C]HCN has been developed. This method was applied to the radiochemical synthesis of a wide range of aromatic 11 C-nitriles in aqueous solutions. The use of readily accessible arylboronic acids as precursors makes this method complementary to the well-established 11 C-cyanation methods that utilize aryl halide precursors.